Bending control of liquid-crystal elastomers based on doped azo derivatives synthesized via controlled gradient polymerization - S. Fitriyani; C. Y. Liu; Y. H. Hung; Y. S. Zhang; J. H. Liu (eXPRESS Polymer Letters)
The intelligence, complexity, and diversification of nature is a continuous source of inspiration for humankind. Imitating natural intelligence to devise bionic microrobots with self-regulated features remains an enormous challenge. Herein, we demonstrate a biomimetic soft material that uses light to trigger mechanical motion. This light-sensitive mimosa mimetic film was designed based on liquid crystal elastomers (LCEs) and photoisomerizable azo compounds. To control the bending direction, a predesigned UV-induced gradient polymerization was used. The energy-controlled polymerized film comprises one high-density and one low-density liquid crystal mesogen face. Similar to mimosas, the fabricated films achieved stimuli-responsive actuation, exhibiting shape deformation upon light illumination. The elastic network undergoes reversible shape changes via photochemical trans-cis isomerization of an azo compound in response to a stimulus. In this study, only a small amount of photoisomerizable 1-Hydroxy-n-(4-nitro-azobenzene-4′-oxy)hexane (AZO) was used; however, the domino effect caused a significant reversible actuation. The mesogen density of the top and bottom faces was found to be an important factor for the bending control. This study explores a new way to fabricate films that can bend in controlled directions during light irradiation. This phototunable film is expected to be used for applications in microrobotics and micromachinery.